Outcomes of a Peritoneal Dialysis Program in Remote Communities Within Colombia - Sanabria, Mauricio (Perit Dial Int, 2015)
♦ Background and Objective: Colombia is a country of diverse geographic regions, some with mountainous terrain that can make access to urban areas difficult for individuals who live in remote areas. In 2005, a program was initiated to establish remote peritoneal dialysis (PD) centers in Colombia to improve access to PD for patients with end-stage renal disease who face geographic or financial access barriers. ♦ Patients and Methods: The present study was a multi-center cohort observational study of prevalent home PD patients who were at least 18 years of age and were being managed by one of nine established remote PD centers in Colombia over a 2-year period. Data were collected from clinical records, databases, and patient interviews. Patient survival, incidence of peritonitis, and rate of withdrawal from PD therapy were assessed. ♦ Results: A total of 345 patients were eligible for the study. The majority (87.8%) of patients lived on one to two times a minimum monthly salary (equivalent to US$243 – US$486). On average, patients traveled 1.2 hours and 4.3 hours from their home to their remote PD center or an urban reference renal clinic, respectively. The incidence rate of peritonitis was 2.54 episodes per 100 patient-months of therapy. A bivariate analysis showed a significantly higher risk of peritonitis in patients who were living on less than one times a monthly minimum salary (p < 0.05) or who had a dirt, cement, or unfinished wood floor (p < 0.05). The 1-year and 2-year patient survival rates were 92.44% and 81.55%, respectively. The 1-year and 2-year technique survival rates were 97.27% and 89.78%, respectively. ♦ Conclusions: With the support of remote PD centers that mitigate geographic and financial barriers to healthcare, home PD therapy is a safe and appropriate treatment option for patients who live in remote areas in Colombia.